Sosialisasi Pemanfaatan Lahan dengan Penanaman Pakan Ternak Ruminansia Berbasis Data Kemampuan Lahan di Kelurahan Kulaba Kota Ternate - Robo, Sarif; Sulasmi, Sulasmi; Hartono, Gunawan (Kadiri University, 2025)
The availability of ruminant feed in Kulaba Village, Ternate City, is still dependent on the seasons, often disrupting livestock productivity. To address this, the community service program aims to increase livestock feed self-sufficiency through outreach and assistance in land use based on land capability data. The method used is a participatory approach, comprising stages of problem identification, spatial analysis of land capability maps, outreach and training, and the construction of demonstration plots (demplots) in yards, rain-fed rice fields, and marginal land. These activities have resulted in an increase in partners' understanding of land map symbols and interpretation, their ability to select forage crops according to land class, and their awareness of the importance of feed preservation through silage technology. Despite these improvements, the main obstacles, such as limited access to seeds, capital, and irrigation facilities, remain. However, the presence of demonstration plots and facilitation by farmer groups has helped accelerate the adoption of technology. As such, this program contributes to strengthening local food security and provides a foundation for the development of sustainable land-use systems in the future. Ketersediaan pakan ruminansia di Kelurahan Kulaba Kota Ternate masih bergantung pada musim, sehingga produktivitas usaha ternak kerap terganggu. Program pengabdian ini bertujuan meningkatkan kemandirian pakan ternak melalui sosialisasi dan pendampingan pemanfaatan lahan berdasarkan data kemampuan lahan. Metode yang digunakan adalah pendekatan partisipatif dengan tahapan identifikasi masalah, analisis spasial peta kemampuan lahan, sosialisasi dan pelatihan, serta pembangunan demonstration plot (demplot) di pekarangan, sawah tadah hujan, dan lahan marginal. Hasil kegiatan menunjukkan peningkatan pemahaman mitra terhadap simbol dan interpretasi peta lahan, kemampuan memilih jenis tanaman pakan ternak sesuai kelas lahan, serta kesadaran pentingnya pengawetan pakan melalui teknologi silase. Hambatan utama masih meliputi keterbatasan akses bibit, modal, dan sarana irigasi, namun adanya demplot dan fasilitasi kelompok tani terbukti mempercepat adopsi teknologi. Program ini berkontribusi dalam memperkuat ketahanan pakan lokal dan memberikan dasar bagi pengembangan sistem pemanfaatan lahan berkelanjutan di masa depan.